KNOWLEDGE OF RISK FACTORS AND WARNING SIGNS OF STROKE AMONGHYPERTENSIVE PATIENTS AGED 18 YEARS AND ABOVE OBTAINING CARE INMUHIMA HOSPITAL, RWANDA - Kibitenga Solange , Kayihura Camille, Dr. Japheths Ogendi (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
Background: In 2019 stroke was the 3rd leading cause of death in Rwanda and accounted for 5.1% of all deaths, Despite efforts by Ministry of Health to control and prevent non-communicable diseases (NCDs),deaths due to stroke rose from the 7th leading cause of death in 2009 to the 3rd in 2019. Aim: This study aims to assess the knowledge of stroke risk factors and warning signs among patients aged 18 years and above receiving hypertension care at Muhima District Hospital, Rwanda. Materials and Methods: This was a cross-sectional study in which a total 247 hypertensive patients aged ≥18 years who were receiving hypertension care at Muhima District Hospital, Rwanda during the month of February were interviewed using self-administered questionnaires. Data was analyzed using SPSS Version 22. Descriptive statistics and multivariable analysis were conducted, with significance considered at P-value < 0.05. Results and Discussions: A total of 247 were interviewed. The level of knowledge of stroke risk factors were as follows: 32% had low knowledge; 25.9% had medium knowledge; and 42.5% had high knowledge. Knowledge level for warning signs were as follows: 42.51% had low knowledge, 34.41% had medium knowledge , and 23.08% had high knowledge. A significant association was found between having no antecedent of stroke at home and knowledge level (P = 0.006). Overall, there was a low significant level of knowledge regarding stroke risk factors. Conclusion: This study examined stroke risk factor and warning sign awareness among hypertensive patients aged 18 and above at Muhima District Hospital's NCD clinic in Rwanda. While many participants showed good knowledge of stroke risk factors, awareness of stroke warning signs was notably deficient, underscoring the necessity for focused educational initiatives to enhance symptom recognition in this group.